The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d1tc01731d
|View full text |Cite
|
Sign up to set email alerts
|

Small radius electron and hole polarons in PbX2 (X = F, Cl, Br) crystals: a computational study

Abstract: The first principles hybrid DFT calculations were performed for small radius polarons - self-trapped electrons (STEL) and holes (STH) in PbX2 (X = F, Cl, Br) crystals, widely used as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Zhang et al reported the effect of polaron formation on the carrier transport properties in cubic phase CsPbI 3 [37]. Mastrikov et al also found the electron and hole polarons in PbX 2 (X = F, Cl, Br) and constructed a clear picture of the corresponding electronic and atomic structures through first-principles calculations [38]. Although much progress has been made in the carriers of perovskite and lead halides, there is little literature on the influence of the pressure on the hot carrier cooling process.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al reported the effect of polaron formation on the carrier transport properties in cubic phase CsPbI 3 [37]. Mastrikov et al also found the electron and hole polarons in PbX 2 (X = F, Cl, Br) and constructed a clear picture of the corresponding electronic and atomic structures through first-principles calculations [38]. Although much progress has been made in the carriers of perovskite and lead halides, there is little literature on the influence of the pressure on the hot carrier cooling process.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the above three main challenges, there are also some concerns in the film fabrication process of IPSCs: it was found that the self-trapped electrons (STEL) and holes (STH) in PbCl 2 and PbBr 2 , which are one of the important components in the formation of all-inorganic perovskite, have an important influence on carrier recombination. Meanwhile, due to the different halogen-halogen distances in CsCl, CsBr, and CsI crystal structure, the temperature for STH migration onset is different, which has an important impact on the PV characteristics of C-IPSCs (as shown in Table 1) [81,82].…”
Section: Exceeding the Solubility Limit Of Cs Saltsmentioning
confidence: 99%
“…Testing these possibilities via spectroscopic methods will clarify the extent to which such defect formation routes are favorable and elucidate their contribution to the phase behavior, but also to the charge carrier dynamics of hybrid perovskites. Such investigation also requires further theoretical work to understand self-trapping effects in photo-active ionic materials [47].…”
Section: Photo De-mixing In Mixed Halide Perovskitesmentioning
confidence: 99%